1984
DOI: 10.1016/s0022-5347(17)49465-1
|View full text |Cite
|
Sign up to set email alerts
|

Dipstick Chemical Urinalysis: An Accurate Cost-Effective Screening Test

Abstract: In a double-blind prospective study of 200 sequential urine specimens the sediment count of leukocytes in the centrifuged urine (white blood cells per high power field) was compared to a chamber count of leukocytes in uncentrifuged urine (white blood cells per microliter.). There was good correlation (coefficient of correlation 0.783, sensitivity 91.9 per cent, specificity 97.6 per cent and efficiency 96.6 per cent) between the more precise chamber count and the more commonly performed sediment count if the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
6

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 14 publications
1
10
0
6
Order By: Relevance
“…Pels et al [4] recommended urinary culture in at least pregnant, diabetic, and elderly patients, as well as institutionalized patients. On the other hand, Oneson et al [2] and Mariani et al [1] found a much lower incidence of false negative results and therefore recommended the dipstick as a cost-effective test. The selection of patients was not given in detail in either of these studies.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Pels et al [4] recommended urinary culture in at least pregnant, diabetic, and elderly patients, as well as institutionalized patients. On the other hand, Oneson et al [2] and Mariani et al [1] found a much lower incidence of false negative results and therefore recommended the dipstick as a cost-effective test. The selection of patients was not given in detail in either of these studies.…”
Section: Letter To the Editormentioning
confidence: 99%
“…In ambulatory patients of general practice medicine, this has proven to be reliable enough, since false negative results are rare in the general population [1,2]. For economical reasons, a dipstick screening without the microscopical evaluation is often performed also in hospitalized patients.…”
mentioning
confidence: 99%
“…The inclusion criteria in our study was a thorough examination within 2 years with no abnormal findings and no urogenital symptoms. Other studies 8,[14][15][16][17] included participant regardless of medical history, urological examinations and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Wegen der hohen Sensitivität etablierter Teststreifen [9,10] sind sie insbesondere zum Mikrohämaturiescreening geeignet. Nachteilig ist lediglich die interindividuelle Schwankungungsbreite von bis zu…”
Section: Testverfahrenunclassified
“…Der Normalwert der Sediment-Gesichtsfeld-Methode weist nach Literaturangaben eine Spannweite von 1-8 Erythrozyten/Gesichtsfeld (Ery/GF) auf (⊡ Tabelle 2), [1,3,12,13,14,15,16]. Die aktuelle amerikanische Leitlinie definiert Hämaturie ab 3 Ery/GF in 2 von 3 Proben -relativiert diesen Grenzwert aber bereits wieder für Patienten mit Risikofaktoren für eine signifikante Erkrankung (s.⊡ Tabelle 1): Wegen der fehlenden unteren Sicherheitsgrenze (no safer lower limit) wird in diesen Fällen empfohlen, bereits ab 1 Ery/GF die Abklärung zu erwägen und bei einer einmaligen Hämaturie ab 3 Ery/GF durchzuführen [1].…”
Section: Grenzwerte Der Mikrohämaturieunclassified